Model-Building as a Philosophical Method - Williamson, Timothy (Phenomenology and Mind, 2019)
The method of building simplified formal models of phenomena under study is widespread in contemporary natural and social science; much scientific progress consists in the provision of better models. A model-building methodology has also been used with success in analytic philosophy, for example by Carnap in his development of intensional semantics. Arguably, philosophers have overlooked how much progress their discipline has made through their failure to conceive it in model-building terms. By using the method more extensively, they can overcome the fragility to error inherent in the naïve falsificationist methodology on which many analytic philosophers rely.